Novel severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) infection: Microbiologic perspectives and anatomic considerations for sanctuary sites - Onyemaechi O. Azu; Samuel O. Olojede; Sodiq K. Lawal; Saheed O. Oseni; Carmen O. Rennie; Ugochukwu Offo; Edwin C.S. Naidu (Elsevier, 2021)
Introduction: A significant chunk of global life - the economy, sports, aviation, academic, and entertainment activities - has significantly been affected by the ravaging outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) with devastating consequences on morbidity and mortality in many countries of the world. Methods: This review utilized search engines such as google scholar, PubMed, ResearchGate, and web of science to retrieve articles and information using keywords like "Coronavirus", "SARS-CoV-2", "COVID-19", "Origin of coronavirus and SARS-CoV-2", "microbiology of coronavirus", "microbiology of SARS-CoV-2", COVID-19", "Coronavirus reservoir sites", "Anatomic sanctuary sites and SARS-CoV-2", biological barriers and coronavirus", biological barrier and SARS-CoV-2". Results: While this pandemic has caught the global scientific community at its lowest level of preparedness, it has inadvertently created a unified and wholesome approach towards developing potential vaccine (s) candidates by escalating clinical trial protocols in many countries of Europe, China and the United States. Interestingly, viral pathobiology continues to be an evolving aspect that potentially shows that the management of the current outbreak may largely depend on the discovery of a vaccine as the administration of known antiviral drugs are proving to offer some respite. Unfortunately, discontinuation and longtime administration of these drugs have been implicated in endocrine, reproductive and neurological disorders owing to the development of pathological lesions at anatomical sanctuary sites such as the brain and testis, as well as the presence of complex biological barriers that permit the entry of viruses but selective to the entrance of chemical substances and drugs. Conclusion: This review focuses on the microbiologic perspectives and importance of anatomical sanctuary sites in the possible viral rebound or reinfection into the system and their implications in viral re-entry and development of reproductive and neurological disorders in COVID-19 patients.